Human immunodeficiency virus infection (HIV)–associated rheumatic manifestations in thepre- and post-HAART eras - Vega, Luis E. (Clin Rheumatol, 2020)
Rheumatic manifestations remain an important clinical manifestation associated to HIV. To date after 4 decades of the onset of the HIV/AIDS pandemic, almost 37 million individuals are living with the infection, including close to 2 million of newly infected individuals. The status, however, of a considerable proportion of HIV/AIDS patients has changed from a near fatal disorder secondary to opportunistic infections to a chronic disease in which renal cardiovascular, diabetes, malignancy, and autoimmune co-morbid disorders have become prevalent and relevant. In addition, the spectrum of rheumatic disorders also has changed since the introduction of HAART and its diagnosis and treatment represents a challenge. The purpose of this review is to define and discuss the HIV-related rheumatic manifestations in the pre- and post-HAART eras.